La direction des sociétés anonymes en droit sénégalais comparée aux droits français anglais et américain - Dieng, Françoise (Université Paris 1, 1995)
Le Sénégal, par la loi n°85-40 du 29 juillet 1985, s'est doté de son premier code des sociétés commerciales depuis son accession à l'indépendance. Cette loi s'inspire des droits français, anglais et américain quant à la direction des sociétés anonymes. C'est à ces droits que sera comparée la direction des sociétés anonymes en droit sénégalais en ses divers aspects que sont les pouvoirs des dirigeants sociaux, leur statut juridique leurs devoirs et leur responsabilité.
Keywords: Approche comparée; Droit commercial; Droit comparé; Droit des sociétés commerciales; Sociétés anonymes; Sénégal

Fiduciary duties of company directors with specific regard to corporate opportunities - Havenga, Michele Kyra (University of South Africa, 1995)
South African company law is currently the object of comprehensive review. One o f the areas under scrutiny is that of corporate governance. Control over management is vital in the interests of the company itself, its shareholders and its creditors. Effective accountability should be balanced against the need to allow those who manage a certain measure of freedom and discretion in the exercise of their function. Company directors are subject to various duties. This thesis concentrates on their fiduciary obligation. It is suggested that this sui generis obligation is owed to the company as a separate entity. Interests of other groups may sometimes merit con sideration. Against the background of a comparative investigation, a "corporate opportunity" is defined as any property or economic opportunity to which the com pany has a claim. South African law protects a company’s claim to an opportunity if it is in the company’s line of business and if the company has justifiably been relying upon the director(s) to acquire it or to assist in its acquisition for the company. The application of established fiduciary principles suffice to resolve corporate opportunity matters. Essentially the application of these rules amount to a determination whether the director has complied with his fundamental duty to act in the company’s best interests. There seems to be no need for a separate doctrine of corporate opportunities.' A director should only be absolved from liability on account of the company’s inability to pursue an opportunity or its rejection by the company if there was no real conflict of interest. The appropriation of corporate opportunities should not be ratifiable, both because the ratification constitutes a fraud on the minority, and because the decision to ratify cannot be regarded as being in the interests of the company. The relationship between the appropriation of corporate opportunities, misuse of confidential information and competition is investigated. These aspects fre quently overlap, but should be distinguished because their bases, and accordingly their appropriate remedies, may differ. Effective control may benefit by a restatement of directors’ fiduciary duties in the Companies Act. To this end certain amendments to the Act are recommended.
Keywords: Codes of conduct; Competition; Confidential information; Conflicts of interest; Corporate opportunities; Corporate opportunity doctrine; Corporation law; Directors of corporations; Fiduciary duties; Multiple directorships; Secret profits

Les Groupes de sociétés et le droit : contribution à la recherche sur la notion de pouvoir en droit privé - Sakho, Abdoulaye (Université Cheikh Anta Diop, 1993)
Keywords: Droit privé; Groupe de sociétés; Pouvoir

Les Etats d'Afrique noire francophone à la recherche d'un droit des sociétés - Gomez, Jean René (Université de Montpellier, 1989)
Keywords: Afrique noire francophone; Corporate law; Droit des sociétés

La constitution des sûretés dans le droit des sociétés commerciales - Brou, Kouakou (Aix-Marseille Université, 1984)
Keywords: Droit des sociétés commerciales; Sûretés (constitution)

La protection des actionnaires minoritaires dans les sociétés de capitaux : en droit français et en droit anglais comparés - Poisson, Marie Danielle (Université Clermont 1, 1984)
Keywords: Actionnaire minoritaire; Droit anglais; Droit comparé; Droit des sociétés commerciales et du GIE; Droit français; Sociétés de capitaux

La continuation des contrats dans la faillite - Hénaff, Jean-Luc (Université de Metz, 1983)
Non disponible
Keywords: Contrat-cadre; Faillite

Skikkings in die Suid-Afrikaanse maatskappyereg - De la Rey, Elisabeth Marie (University of Pretoria, 1983)
Die doel van hierdie proefskrif was om bestaande prohleme in verband met maatskappyregtelike skikkings te ondersoek, in die lig daarvan dat die prosedure berug is as n wyse om misdadige bedrywighede rondom die ineenstorting van n maatskappy te verberg. Die ondersoek is hoofsaaklik beperk tot skikkings, hoewel skikkings en reelings deur dieselfde bepalings van die Wet gereguleer word. Die geskiedkundige ontwikkeling van artikels 311 en 312 is vanaf hul ontstaan in die Engelse wetgewing nagegaan. Die begrippe "skikking" en "reeling" is ontleed en die praktiese gebruike daarvan nagegaan. l Ons howe beskou n goedgekeurde maatskappyregtelike skikking as n kontrak; dit voldoen egter nie aan die vereistes vir n kontrakregtelike skikking nie. Die tersaaklike kontraktuele aspekte is derhalwe nagegaan. Aan die hand van regspraak en n aantal goedgekeurde skikkings, is die inhoud van n skikkingsaanbod ontleed. Die toepaslike prosedure en formaliteite is sorgvuldig nagegaan, in die lig daarvan dat die Wet eerder hierop klem 1~ as op die inhoud van die skikking. Besondere aandag is aan die grondslag vir indeling van skuldeisers en lede in verskillende klasse gegee. Statutere regulering van die skikkingprosedure eindig nadat die skikking van krag geword het. Die verdere verloop vind in ooreenstemming met die bepalings van die skikking plaas. Uitvoering hiervan word deur n sogenaamde ontvanger namens skuldeisers waargeneem, n amp wat nog nie statutere erkenning geniet nie, maar wat in die praktyk duidelik uitgekristalliseer het. Aan die hand van regspraak is sy amp verder nagegaan en is daar aanbeveel dat, net soos in Australie, sy amp statuter erken en gereel behoort te word. Daar is gelet op misbruik van die skikking- en reelingskemaprosedure, sowel as op die behoefte aan beter beskerming van skuldeisers en lede. Daar is aanbeveel dat waar n maatskappy in likwidasie of onder ,geregtelike bestuur is, skikkings uit die artikel 311-prosedure gelig behoort te word en in ooreenstemming met die akkoordprosedure by insolvensie gebring te word, met die verskil dat likwidasie of geregtelike bestuur onmiddellik by bekragtiging van n skikking opgehef kan word. Yoldoende tyd vir behoorlike ondersoek van n maatskappy se sake behoort toegelaat te word alvorens n skikking oorweeg kan word en meer omvattende inligting behoort aan skuldeisers en lede verskaf te word. Die howe behoort in die uitoefening van hul diskresie deur n deskundige bygestaan te word wat oor die ekonomiese aspekte van n skema verslag doen.
URI: https://repository.up.ac.za/handle/2263/41935
Keywords: Corporate law; Die geskiedkundige ontwikkeling van artikels 311 en 312; Droit des sociétés; Maatskappy; Maatskappyregtelike skikkings; South Africa

The personal fiduciary character of members' inter se relations in the incorporated partnership - Ribbens, Daniel S. (McGill University, 1982)
Corporation characterized by members' freedom from liability for corporate debts, and partnership, characterized by inter se relations of mutual confidence and good faith, are polar types. Over the ages a host of hybrid types has evolved between those polar types. In the incorporated partnership–the final stage of that evolution–partnership and corporation coalesce. American and German law recognize the personal fiduciary character of corporate partners' inter se relations for the purpose of enforcing fiduciary duties. Anomalously, English company law recognizes that character under the statutory just and equitable winding-up provision but not for the purpose of enforcing fiduciary duties. A case may therefore be made for recognizing fiduciary duties between corporate partners.
https://escholarship.mcgill.ca/concern/theses/sf268602w
Keywords: Corporate debt; Incorporated partnership; Personal fiduciary

Le régime des sociétés d'économie mixte en Haute-Volta - Sawadogo, Filiga Michel (Université Paris 1, 1981)
Keywords: Burkina Faso; Economie mixte; Haute-Volta; Société

The raising and maintenance of capital : a comparative study of some problems in the law of corporation finance - Ponnuswami, K. (McGill University, 1969)
This the sis is an in-depth comparative study and critical examination of several wide-ranging problems in the law of corporation finance of Britain and the principal jurisdictions of Canada and the United States of America. The problems examined include inadequate Capitalization, Stock-watering, Reduction of Capital, Purchase by a Corporation of its Shares, and Dividends. The the sis examines the trends and patterns in the different jurisdictions and appraises their merits and defects. The study concludes that the conceptual ambiguities and practical difficulties which abound in the laws of corporation finance are aggravated by the failure of the law to work out rational rules based on a clear and unifying policy for the raising and maintenance of capital. The necessity for such a policy is advocated in view of the inadequacy of the existing institutions and devices for the protection of the multifarious interests involved in corporate business enterprises. Cette thèse se présente sous la forme d'une étude comparative en profondeur et d'un examen critique de quelques problèmes du droit des corporations financières de Grande Bretagne et des principales juridictions du Canada et des Etats-Unis d'Amérique. Y sont étudiés entre autres l'insuffisance de capital, la dilution de capital, la réduction de capital, le rachat de ses actions par une corporation et les problèmes concernant les dividendes. On y examine ensuite les tendances et positions de ces différentes juridictions, pour en évaluer les mérites et les défauts. En conclusion cette étude montre que les ambiguités conceptuelles et les difficultés pratiques qui abondent dans le droit des corporations financières sont aggravées par l'insuffisance de la loi à élaborer de règles rationnelles, basées sur une politique claire et uniforme de souscription et de maintien du capital. La nécessité d'une telle politique semble évidente lorsque l'on considère l'imperfection des institutions actuelles et des moyens de protection des multiples intérêts impliqués dans les corporations commerciales.
https://escholarship.mcgill.ca/concern/theses/cv43nx97w
Keywords: Capitalization; Corporations; Finance; Reduction of capital; Shares